Reciprocal Interactions Between Gut Microbiota and Host Social Behavior - Münger, Emmanuelle; Montiel-Castro, Augusto J.; Langhans, Wolfgang; Pacheco-López, Gustavo (Frontiers in Integrative Neuroscience, 2018)
Animals harbour an extensive, dynamic microbial ecosystem in their gut. Gut microbiota (GM) supposedly modulate various host functions including fecundity, metabolism, immunity, cognition and behaviour. Starting by analysing the concept of the holobiont as a unit of selection, we highlight recent findings suggesting an intimate link between GM and animal social behaviour. We consider two reciprocal emerging themes: i) that GM influence host social behaviour and ii) that social behaviour and social structure shape the composition of the GM across individuals. We propose that, throughout a long history of coevolution, GM may have become involved in the modulation of their host’s sociality to foster their own transmission, while in turn social organization may have fine-tuned the transmission of beneficial endosymbionts. We suggest that investigating these reciprocal interactions can advance our understanding of sociality, from healthy and impaired social cognition to the evolution of specific social behaviours and societal structure.